PENCABUTAN DINI GIGI SULUNG AKIBAT CARIES GIGI DAPAT MENYEBABKAN GIGI CROWDING - Ni Luh Putu Suarniti (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2014)
Primary teeth are the teeth while the children who will be replaced by permanent teeth. By a variety of causes, primary teeth are not able to function so that the necessary action is premature retraction. Early lifting of deciduous teeth caused by many factors, some of them by dental caries. The prevention can be done to maintain the baby teeth are Topical Fluoride Application, Fissure Sealant, and Orthodontic Interceptive. Although temporary, the child's primary teeth also require treatment, such as tooth extraction eldest, eldest dental fillings, and root canal treatment in primary teeth. These things are done to avoid the occurrence of dental crowding or over‐crowded teeth.